Pengaruh Kecemasan Matematika Siswa Kelas VII Terhadap Hasil Belajar Di SMP Negeri 3 Kota Bengkulu - Nopela, Lola Anggun; Lestari, Amelia; Lorenza, Sintia; Syafri, Fatrima Santri (Pendidikan Matematika Universitas PGRI Yogyakarta, 2020)
This research is a study that discusses the influence of mathematics on grade VII students—learning outcomes at SMP NEGERI 3 Kota Bengkulu. This study's population was all students of class VII SMP NEGERI 3 Bengkulu City, which consisted of 130 famous students in 5 classes. Samples were taken using the random sampling technique. Then, a sample of class VII.2 was chosen, possibly 20 students. This study using a questionnaire and documentation. The data were obtained using a questionnaire, while the documentation in this study was used to obtain learning data obtained from teacher data in the form of daily math test scores. In the research analysis, prerequisite tests were used, such as the normality test, linearity test, and product moment test with SPSS version 22. The analysis results obtained a value of 0.754, which indicates that the relationship's level is healthy between the two variables. There is a positive sign indicating that the property is valuable. Positive and unidirectional. The results of the analysis using Pearson products when the significance value was obtained 0.000. The results of this study indicate that there is a significant relationship between the effect of mathematics on learning outcomes at SMP NEGERI 3 Kota Bengkulu.Keywords: Mathematics anxiety, learning outcomes